2022
DOI: 10.1161/hypertensionaha.122.19072
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Benefits and Risks of Using a Reduced-Sodium, Potassium-Enriched Salt Substitute in India: A Modeling Study

Abstract: Background: Salt substitution (ie, replacement of table and cooking salt with potassium-enriched salt substitutes) is a promising strategy to reduce blood pressure and prevent cardiovascular disease, particularly in countries like India where there is high sodium intake, mainly from discretionary salt, and low potassium intake. Life-threatening hyperkalemia from increased potassium intake is a postulated concern for individuals with chronic kidney disease. methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…[5][6][7] Additionally, potassium-containing salts have been used as substitutes for sodium. [8][9][10] Many studies have shown that high potassium intake may lower blood pressure and CVD risk partly, [11][12][13] and high potassium intake may mitigate the negative impacts of high sodium intake. 14 Cognitive impairment is linked to cardiovascular risk factors in the general population, 15 and diet is considered an important factor in cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Additionally, potassium-containing salts have been used as substitutes for sodium. [8][9][10] Many studies have shown that high potassium intake may lower blood pressure and CVD risk partly, [11][12][13] and high potassium intake may mitigate the negative impacts of high sodium intake. 14 Cognitive impairment is linked to cardiovascular risk factors in the general population, 15 and diet is considered an important factor in cognitive function.…”
Section: Introductionmentioning
confidence: 99%
“…A second pivotal study is reported in this issue of Hypertension. 2 The researchers modeled the effects of a population-wide intervention in India replacing salt with a potassium enriched salt substitute as used in the China study. The modeling study evaluated the impact of this intervention on cardiovascular disease morbidity and mortality as well as adverse effects from hyperkalemia both in the general population and in those with undiagnosed chronic kidney disease.…”
Section: See Related Article Pp 2188-2198mentioning
confidence: 99%
“…23 Importantly, the nationwide implementation of salt substitution could lead to potential benefits, such as the prevention of approximately one in nine cardiovascular deaths in China, 44 and avoid 8%-14% of annual cardiovascular deaths in India. 45 These findings are relevant to the Australian CALD community, where Australians born overseas in India and China make-up 5% of the total population. 46 Notably, over 40% of our survey respondents had previously heard of or had used a salt substitute, which was higher than the 5.9% of participants in the SSaSS 23 and none in the SSiIS study.…”
Section: Discussionmentioning
confidence: 89%
“…The China Salt Substitute and Stroke Study (SSaSS) demonstrated that using potassium‐enriched salt substitute significantly lowers the risk of stroke by 14% and death by 12% among 20 995 Chinese individuals 23 . Importantly, the nationwide implementation of salt substitution could lead to potential benefits, such as the prevention of approximately one in nine cardiovascular deaths in China, 44 and avoid 8%–14% of annual cardiovascular deaths in India 45 . These findings are relevant to the Australian CALD community, where Australians born overseas in India and China make‐up 5% of the total population 46 .…”
Section: Discussionmentioning
confidence: 99%